2015
DOI: 10.1111/1346-8138.12758
|View full text |Cite
|
Sign up to set email alerts
|

Cystic trichoblastoma: A report of two cases with an immunohistochemical study

Abstract: We herein report two cases of cystic trichoblastoma with an immunohistochemical study. The histopathological findings in these cases included new information, namely, their being composed of two and three cysts, the cystic components had features of a steatocystoma and a hybrid cyst in one case, and there were projections of an aggregation of trichoblastoma, as well as papillary projections of follicular germinative cells, from the cyst walls. The follicular germinative cells observed in the papillary projecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The authors suggested that the presence of aggregations of follicular germinative cells with fibrotic stroma, similar to that of the follicular papilla, supported a neoplastic, rather than a cystic, nature of this lesion. Moreover, Misago et al reported an additional two cases of CTB and showed positive findings in the aggregations for Ber‐EP4 and the markers of follicular stem cells, including CK15 and PHLDA1 . These findings suggested that CTB is a unique type of trichoblastoma which originates from the cyst wall of an infundibular cyst.…”
Section: Discussionmentioning
confidence: 96%
“…The authors suggested that the presence of aggregations of follicular germinative cells with fibrotic stroma, similar to that of the follicular papilla, supported a neoplastic, rather than a cystic, nature of this lesion. Moreover, Misago et al reported an additional two cases of CTB and showed positive findings in the aggregations for Ber‐EP4 and the markers of follicular stem cells, including CK15 and PHLDA1 . These findings suggested that CTB is a unique type of trichoblastoma which originates from the cyst wall of an infundibular cyst.…”
Section: Discussionmentioning
confidence: 96%
“…The cyst wall resembles the follicular infundibulum, and the cavity is filled with lamellar orthokeratosis (Figure 4). 5,11 Epidermal inclusion cysts also contain a cyst wall that resembles the infundibular epithelium, without differentiation to all segments of the hair follicle. They are lined by a stratified squamous epithelium, retain a granular layer, and contain lamellar keratin within the cyst cavity.…”
mentioning
confidence: 99%
“…In patients with an upper eyelid nodule, histopathological examination should differentiate among cystic BCC, AH, cystic trichoblastoma, BCC with ductal and glandular differentiation, and BCC occurring in an infundibular cyst. [3][4][5] BCC with ductal and glandular differentiation and AH usually show the findings of differentiation towards apocrine glands. Cystic trichoblastoma usually originates from infundibular cyst and have fibrous interstitium and structures like follicular germinative cells.…”
mentioning
confidence: 99%